Do neoprene sleeves and prophylactic knee braces affect neuromuscular control and cutting agility?. (September 2019) - Bodendorfer, Blake M.; Arnold, Nicholas R.; Shu, Henry T.; Leary, Emily V.; Cook, James L.; Gray, Aaron D.; Guess, Trent M.; Sherman, Seth L.
Abstract: Objectives: To evaluate the effects of neoprene sleeves (NSs) and prophylactic knee braces (PKBs) on neuromuscular control and cutting agility. Design: Markerless motion-capture technology tracked subjects (1) without a brace as a control (2) with NSs and (3) with PKBs during single-leg drop vertical jump (SLDVJ), single-leg squat (SLS), Y-excursion, and cutting movements. Movements were recorded five times per bracing condition in three different sessions. Setting: University laboratory. Participants: Ten healthy, active subjects (5 male, 5 female; age range, 22–26 years). Main outcome measures: Degrees of motion and time to completion. Results: Use of NSs and PKBs reduced subjects' hip internal rotation in the loading phase of SLDVJ (p = 0.026, 0.02) and SLS (p = 0.005, <0.001), reduced knee flexion in the loading phase of SLDVJ (p = 0.038, <0.001), and reduced knee frontal plane abduction (FPA) with SLS (p = 0.015, 0.024) and Y-excursion (p = 0.002, 0.005) compared to control. Use of PKBs decreased subjects' hip internal rotation in the Y-excursion (p = 0.024) and reduced knee FPA in the SLDVJ loading phase (p = 0.014) compared to control. There was no difference in cutting agility for either group (p = 0.145, 0.347). Conclusion: Both NSs and PKBs positively impacted neuromuscular control without impacting cutting agility. Highlights: Neoprene sleeves (NSs) and prophylactic knee braces (PKBs) reduced dynamic valgus. Use of NSs and PKBs improved neuromuscular control during dynamic movement. Use of NSs and PKBs did not reduce one's cutting agility.